¬¬Perancangan Interior Lounge & Bar di Surabaya - Nandya Mareta Liwijaya; Stephanus P Honggowidjaja; Hendy Mulyono (Intra, 2016)
Surabaya City is a city that is experiencing industrial and economic progress very rapidly. Interaction space shrinking, and impetus to a new atmosphere amid dense activity for relaxing themselves, thus encouraging the displacement space of interaction of an office or residential to public places. The growth of young people in Surabaya is increasing, which produce a new lifestyle, diverse lifestyle of young people today is heavily influenced by the lifestyle of western culture so that the necessary places which facilitate business activities in social space, especially for the young executive.